Media agendas, public opinions and elections : evidence from Ireland and the United Kingdom - Zalinski, Zbigniew (Trinity College (Dublin, Ireland). Department of Political Science, 2010)
This dissertation analyses the news media coverage of the 2005 general election campaign in the United Kingdom and the 2007 general election campaign in Ireland. The study also investigates the public opinion in those countries during the election campaigns and explores the possible relationship between media and public agendas. It compares the media and public agendas across countries.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin.